Competences and the brazilian journalist education: thinking upon new learning methodologies - Kalume Maranhão, Ana Carolina (2016)
The hability to articulate graduation disciplines through new learning methodologies based on projects, as Project Based Learning (PBL) and the accomplishment of the researches projects comprises the necessary knowledge bases for the improvement of the learning and teaching relation that is required by the graduating student in an implantation scenery of the new National Curriculum Directives for the Journalism courses in the Brazilian universities. Therefore, in the context of this work, the competences concept is studied as part of a new process, that meets its highest point in the 21st Century, due to the tecnological innovation, Information Technology development and the deep chance in the Brazilian journalist professional practices.